Investigation on the processing - microstructure - property relationship of 3D-printed thermoplastic polyurethane - Russell, Eber Perry (Nanyang Technological University, 2021)
Additive manufacturing (AM) or more commonly known as 3D printing, has become the preferred choice of manufacturing for multiple industries due to its versatility, accurate dimensions and reduced resources used. AM is a systematic process of extracting precise 3D computer-aided designs via computer-aided design (CAD) softwares, followed by building it up layer by layer. There are several methods of AM and this study will be focusing on Powder Bed Fusion, more specifically Selective Laser Sintering (SLS) and investigating the processing-microstructure-property relationship of 3Dprinted thermoplastic polyurethane, mainly L-TPU and P-TPU. This article begins with an introduction to the SLS technique and the two TPU powders used, following with the methodology and different types of testing methods used, ranging from mechanical and thermal properties to the chemical structure (microstructure) of the respective thermoplastic polyurethanes. This study aims to investigate the processing-microstructureproperty relationship of TPU by evaluating test results from differential scanning calorimetry (DSC) tests, thermogravimetric analysis (TGA) tests, compression tests, micrographs, microCT and tensile tests. This study will conclude with a discussion about the co-relation of these three elements, such as how the energy density can influence the mechanical properties of TPU and how the two distinct chemical structures of the two TPU powders can vary in properties such as elastic modulus and its ability to withstand different amounts of stress.